2009
DOI: 10.1002/syn.20627
|View full text |Cite
|
Sign up to set email alerts
|

The neurokinin‐3 (NK3) and the neurokinin‐1 (NK1) receptors are differentially targeted to mesocortical and mesolimbic projection neurons and to neuronal nuclei in the rat ventral tegmental area

Abstract: Tonic activation of neurokinin-3 (NK3) receptors in dopamine neurons of the ventral tegmental area (VTA) has been implicated in the pathophysiology of schizophrenia. This psychiatric disorder is associated with a dysfunctional activity in VTA projection neurons that can affect cognitive function at the level of the medial prefrontal cortex (mPFC) as well as motor and motivational states controlled in part by mesolimbic output to the nucleus accumbens (Acb). To determine the relevant sites for NK3 receptor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…In SON and PVN, immunoreactivity for NK3-R observed with either confocal or electron microscopy has a clustered appearance in the neuronal nuclei (Howe et al, 2004; Haley and Flynn, 2006; Jensen et al, 2008). The nuclear immunoreactivity for NK3-R reported in globus pallidus and VTA has a similar clustered appearance (Levesque et al, 2006; Lessard et al, 2009). This clustered appearance is consistent with localization of NK3-R to nuclear suborganelles some of which are rich in histones (Handwerger and Gall, 2006; Misteli, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…In SON and PVN, immunoreactivity for NK3-R observed with either confocal or electron microscopy has a clustered appearance in the neuronal nuclei (Howe et al, 2004; Haley and Flynn, 2006; Jensen et al, 2008). The nuclear immunoreactivity for NK3-R reported in globus pallidus and VTA has a similar clustered appearance (Levesque et al, 2006; Lessard et al, 2009). This clustered appearance is consistent with localization of NK3-R to nuclear suborganelles some of which are rich in histones (Handwerger and Gall, 2006; Misteli, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…DOP may play a role in clinical comorbidities to pain (e.g., depression and anxiety) and has recently been implicated in the facilitation of CPP induced by morphine but not reinforcement, indicating a role in contextual cues (Lutz and Kieffer, 2013). The interdependency of opioid receptors with the neurokinin system in reward/motivation pathways (Lessard et al, 2009;Commons, 2010) is reported. SP administration induces CPP, whereas NK 1 receptor antagonism decreases morphine reinforcement in self-administration studies (Holzhauer-Oitzl et al, 1988;Placenza et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…For example, under basal conditions, NK3R is found within the nucleus of neurons in the ventral tegmental area of rat (VTA) (40) and globus pallidus of squirrel monkeys (41). Limited NK3R is found in nuclei of SON neurons under basal conditions, but nuclear NK3R increases significantly in response to hypotension (26).…”
Section: Discussionmentioning
confidence: 98%
“…Although the present focus is on the PVN, the same may apply to multiple other brain regions that express NK3R. Indeed, NK3R is detected within the nuclei of neurons in the globus pallidus and ventral tegmental area (40,41). Additional techniques were not used to identify whether nuclear NK3R in these brain areas associated with transcriptionally active chromatin, but the presence of the NK3R in nuclei of neurons in a variety of brain regions suggests that NK3R may affect gene activation under multiple conditions.…”
Section: Perspectives and Significancementioning
confidence: 89%